PHYSICOCHEMICAL OF PEARL MILLET (Pennisetum glaucum (L.) R. Br.) STARCH MODIFIED BY HEAT MOISTURE TREATMENT - Retno Widyastuti (Journal of Food and Agricultural Product, 2021)
Millets have a high enough starch content so it can be used as an alternative source of carbohydrates. Native millet starch is known less stable against stirring and heating so it is necessary to improve starch properties by modification of starch. In this study, the character of modified millet starch heat moisture treatment (HMT) evaluated with variations treatment of temperature and heating time. Millet starch was conditioned to a moisture content of 25% and heating at 100, 130 and 150 0C for 3, 5 and 7 hours in oven. Chemical properties (water content and amylose content) and physical properties (solubility and swelling). The results showed that modification caused a decrease in the solubility and development of starch. Modification of millet starch with HMT changed the starch paste profile more stable.